Usefulness of Practitioner-Led Pancreatic Cancer Screening - Kazuya Matsumoto; Yoshinori Kushiyama; Akio Izumi; Koji Ohnishi; Masahiko Miura; Yasufumi Ohuchi; Ikuko Hori; Tomonori Nakamura; Kotaro Hori; Kenji Koshino; Junko Kobayashi; Nagisa Yoshino; et al. (Diagnostics, 2022)
The 5-year survival rate for pancreatic cancer has improved (10%) but remains worse than that for other cancers. Early pancreatic cancer diagnosis is challenging, and delayed diagnosis can delay treatment, which impairs survival. Practitioners do not promptly refer cases to a general hospital, causing delayed discovery. Herein, we aimed to examine the usefulness of the Pancreatic Cancer Project in Matsue, whose objective is to detect pancreatic cancer in patients presenting at any medical institution in Matsue City. Clinical data were extracted from medical records, and abdominal ultrasonography and tumor marker blood level assessments were performed (n = 234; median age, 71 [range, 41–94] years; 51% male). Cases with abnormal abdominal ultrasonography or blood test findings were referred for specialist imaging and followed up. The pancreatic cancer detection rate was 6.0% (n = 14); all cases were referred to a general hospital by practitioners within 1 month. Patients had stage IA (n = 1), IIA (n = 6), IIB (n = 2), III (n = 1), and IV (n = 4) disease. Overall, pancreatic cancer could be detected at an earlier stage (I–II), but referral to a general hospital by visiting practitioners should be prompt. The Pancreatic Cancer Project in Matsue may help improve the detection and prognosis of pancreatic cancer.